Evaluation of Masticatory Function, Satisfaction, and Quality of Life Among Users of Complete Dentures Relined with Resilient Materials: A Systematic Review - Santiago, Jeferson Batista; Leão, Rafaella De Souza; Pellizzer, Eduardo Piza [UNESP]; do Egito, Belmiro Cavalcanti; de Moraes, Sandra Lúcia Dantas (Quintessence Publishing, 2024)
Purpose: To evaluate whether complete dentures (CDs) relined with long-term resilient liners (LTRLs) favor better masticatory function, satisfaction, and quality of life among completely edentulous patients compared to conventional CDs. Materials and Methods: This review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) checklist and was registered in PROSPERO (the International Prospective Register of Systematic Reviews; CRD42021258700). The population, intervention, comparison, and outcome (PICO) purpose was to determine whether CDs relined with LTRLs favor better masticatory function, satisfaction, and quality of life among completely edentulous patients when compared to CDs. Searches were performed in the PubMed/MEDLINE, Embase, Scopus, Lilacs, BBO, and OpenGrey databases. Manual searches were also performed to identify additional primary studies. Results: Overall, 3,953 articles were found. After removing duplicates, reading the articles, and applying the inclusion and exclusion criteria, 15 articles were selected for qualitative analysis, totaling 422 patients with follow-up periods ranging from 1 week to 3 years. Among these, 8 studies assessed masticatory function using different methods, 2 assessed satisfaction, 1 assessed quality of life, and 4 assessed more than one outcome. Through qualitative analysis, LTRLs showed satisfactory results in most studies when compared to CDs in relation to masticatory function, satisfaction, and quality of life. Conclusions: LTRLs favor better masticatory function, satisfaction, and quality of life among completely edentulous patients compared to CDs